The IMPROVMENT OF STUDENTS 'MATHEMATIC COMUNICATION ABILITY THROUGH GERLACH AND ELY LEARNING MODELS IN SMP IT BAITUL QURAN LANGSA - Priyanda R (Jurnal Dimensi Matematika, 2020)
The purpose of this study is to examine: Improvement of mathematical communication skills of students who obtain Gerlach and Ely learning is better than mathematical communication skills of students who obtain conventional learning, The relationship between students' initial mathematical abilities with Gerlach and Ely learning towards communication skills mathematical, but the relationship between students' mathematical communication skills with student mathematics learning outcomes. This research is a semi-experimental research. The population of this study were all IT students Baitul Quran Langsa, amounting to 22 students where 15 students were in class VII and 7 students were in class VIII. Then the two classes are given different treatment of the learning model. The experimental class was treated with Gerlach and Ely learning and control classes with conventional learning. The instrument used consisted of: a test of mathematical communication skills. The instrument was stated to have fulfilled the content validity requirements, and the reliability coefficient was 0.87. Data analysis was performed with the t-test statistical test, bivariate correlation test and 2-way anova test. Based on the analysis results obtained by the results of the study are: an increase in mathematical communication skills of students who get Gerlach and Ely learning better than students who obtain conventional learning, there is no interaction between learning with students 'initial ability to increase students' mathematical communication skills, there is a positive relationship between students' mathematical communication skills and student mathematics learning outcomes. Descriptively the answers to the problem formulation were also examined, namely: the process of solving students' answers whose learning with Gerlach and Ely learning was neater and more complete based on indicators of mathematical communication skills compared to students who used conventional learning. Based on the results of the study, the researchers suggest: Gerlach and Elypada learning of mathematics to improve students' mathematical communication skills can be used as an alternative to applying varied and innovative mathematics learning.